KOMUNIKASI MAHASISWA MUSLIM INDONESIA DI BEIJING - Ulfa Khairina (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) Ar-Raniry, 2017)
The Indonesian Muslim students in China is one of a small community who faced communication barrier while study in China. The communication barrier in Beijing was conducted by local situation. This research conducted by descriptive research approach by using indepth interwiviwe to find how Indonesian Muslim students in China manage all barrier. The research found that the Indonesian students in Beijing have solved their problem by joined with Indonesian Students association.